Effects of the Spanish War of Independence on United States Policy - Almudena HERNÁNDEZ RUIGÓMEZ (Cuadernos Dieciochistas)
This study deals with the repercussions of the Spanish-French conflict on the other side of the Atlantic, and in particular, the United States, taking into account the role of France and England in the establishment of intercontinental relations. The territorial, strategic and commercial advantages obtained by the US are also analysed.